FEATURES OF QUALITY SYSTEMS IN HIGHER EDUCATION INSTITUTIONS - Nigmatov Rutfullo Olimdjanovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article states that the changes caused by reforms in the educational system, including higher education, have great historical significance in socio-political, legal, economic and spiritual terms, that the reforms carried out not only led to great positive changes in our country, but even in the international arena brought our country's reputation to a new level. It is also expressed in the need to seriously approach the issues of development of the educational system, improving the skills and prestige of educators in society, raising the morale of the younger generation, adapting the spiritual and educational environment to the demands of the time, raising the teacher's profession, prestige, educating new age educators, developing pedagogical science, bringing great attention to the introduction of innovative